A capture–recapture model of amphidromous fish dispersal. Issue 4 (12th February 2014) - Smith, W. E.; Kwak, T. J.
<x xml:space="preserve">Abstract</x> Adult movement scale was quantified for two tropical Caribbean diadromous fishes, bigmouth sleeper Gobiomorus dormitor and mountain mullet Agonostomus monticola, using passive integrated transponders (PITs) and radio‐telemetry. Large numbers of fishes were tagged in Río Mameyes, Puerto Rico, U.S.A., with PITs and monitored at three fixed locations over a 2·5 year period to estimate transition probabilities between upper and lower elevations and survival probabilities with a multistate Cormack–Jolly–Seber model. A sub‐set of fishes were tagged with radio‐transmitters and tracked at weekly intervals to estimate fine‐scale dispersal. Changes in spatial and temporal distributions of tagged fishes indicated that neither G. dormitor nor A. monticola moved into the lowest, estuarine reaches of Río Mameyes during two consecutive reproductive periods, thus demonstrating that both species follow an amphidromous, rather than catadromous, migratory strategy. Further, both species were relatively sedentary, with restricted linear ranges. While substantial dispersal of these species occurs at the larval stage during recruitment to fresh water, the results indicate minimal dispersal in spawning adults. Successful conservation of diadromous fauna on tropical islands requires management at both broad basin and localized spatial scales.